Laboratory Investigation of Cement Treated Bases (CTB) and Full-depth Reclamation (FDR) Mixes. - Kumar, Rohan (My University, 2022)
In the last decades, new road melioration technologies have evolved to abate the utilization of aggregates in new pavement, this helps in abating the construction cost, decimation of natural resources as well as curtailing of energy. This study provides an innovative approach to determining the per cent of cement added for the base course stabilisation along with the certain percentage of class C fly ash and to study the engineering properties of the stabilized mix. Also, with the application of FDR, an effective approach was made to improve the strength of reclaimed pavement material (RPM) by the utilization of TerraCil & ZycoBond, chemical commercial stabilizers along with a certain percentage of cement to reduce moisture damage (water permeability) and enhance the flexibility enabling dimensionally stable non-deforming base. Due to the use of various cement percentages and chemical stabilisers in the case of FDR, aspects related to compaction, durability, and unconfined compressive strength (UCS) are examined. The UCS increased substantially with the addition of different cement per cent in the CTB mix but decreases on increasing fly ash content and stabilizers along with cement in FDR. There was an average mass loss of 5.80% in 12 cycles of wetting-drying have been observed in the durability test of the CTB mix designed. This study shows how it is beneficial to use the cement-treated base to replace the conventional base material used for the construction of high-volume and low volume-roads. According to the analysis of the sections that were designed, a thicker wearing course is needed because the granular layer's strength is poor in order to prevent roads from failing due to rutting and cracking. There is a significant difference in the cost of construction of wearing course and other layers of flexible pavement. Due to the higher modulus of Cement Treated Base (CTB), the thickness of CTB is significantly less than Granular Base (GSB) layer for same traffic count. CTB is the better alternative to conventional granular base. So, an attempt has been made to investigate the cost of the construction of flexible pavement designed with CTB as a base layer for 50 msa traffic for high-volume roads and 5 msa traffic for low-volume roads. IRC: 37 (2018) was followed to estimate the thickness of different layers of flexible pavement. The cost per kilometre of a road having a flexible pavement designed with CTB base layer was reduced by 24.48% for high-volume roads and 34.20 % for low-volume ones. Further, with the application of FDR, a cost reduction of 30.06% was indicated in the low-volume roads.
Keywords: CTB; FDR; Modulus; Durability; Cost Analysis; Design